2012
DOI: 10.1007/s13277-012-0344-0
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of serum carcinoembryonic antigen as an indicator of brain metastasis detection in advanced non-small cell lung cancer

Abstract: Although many biomarkers have emerged in non-small cell lung cancer (NSCLC), the predictive value of site-specific spread is not fully defined. We designed this study to determine if there is an association between serum biomarkers and brain metastasis in advanced NSCLC. We evaluated 227 eligible advanced NSCLC patients between May 2005 and March 2010. Patients who had been newly diagnosed with stage IV NSCLC but had not received treatment previously, and had available information on at least one of the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 23 publications
0
47
0
Order By: Relevance
“…Our previous study suggested that integration of surrogate markers such as LDH and albumin, which were confirmed as independent prognostic factors for survival, should be examined in greater detail and large databases [7]. Before proceeding with such efforts, we were interested in other potential biomarkers, in particular tumor markers, which have already been shown to correlate with risk of development of brain metastases [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study suggested that integration of surrogate markers such as LDH and albumin, which were confirmed as independent prognostic factors for survival, should be examined in greater detail and large databases [7]. Before proceeding with such efforts, we were interested in other potential biomarkers, in particular tumor markers, which have already been shown to correlate with risk of development of brain metastases [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, studies suggested that abnormal serum neuron-specific enolase (NSE), cancer antigen (CA) 125, and carcinoembryonic antigen (CEA) were independent risk factors for metachronous brain metastases in patients with initial stage III non-small cell lung cancer (NSCLC) [8,9] and that CEA levels had statistically strong associations with brain metastases in patients with stage IV or IIIB/IV disease [10,11]. On the other hand, their prognostic impact after diagnosis of brain metastases is poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the whole-body metastatic extent, we applied the total metastatic scoring system in the same manner as in our previous studies [19][20][21]. Synchronous metastatic sites were categorized into seven groups as follows: abdomen/pelvis (including adrenal gland, abdomino-pelvic lymph nodes, and other abdominal or pelvic organs), lung-to-lung or pulmonary lymphangitic spread, bone (skeletal system), pleura and/or pleural effusion and/or pericardial effusion, neck and/or axillary lymph nodes, other soft tissue, and brain.…”
Section: Review Of Metabolic Imaging To Evaluate Metastatic Charactermentioning
confidence: 99%
“…In a perspective study enrolling 293 patients with staged IIIB-IV NSCLC also found, CEA ≥ 40 ng/ml was an independent risk factor of BM [26]. In another prospective study conduced by Lee et al, the association of tumor markers including CEA, Cyfra21-1, CA125, CA199 and SCC and BM were studied in 227 patients with advanced NSCLC [27]. As a result, CEA level was the only tumor marker that was found to be significantly different between patients with BM and without BM.…”
Section: Discussionmentioning
confidence: 98%